Unbounded branches of solutions of some boundary-value problems - Dymarskii, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For nonlinear equations of a special type, in the case of double degeneration of a linearized problem, we prove the existence of unbounded branches of solutions originating at a bifurcation point.